1980
DOI: 10.1063/1.328171
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous behavior in the radiation pattern of piezoelectric transducers induced by parasitic Lamb wave generation

Abstract: In order to improve ultrasonic image quality, transducers, similar to those currently used in nondestructive testing and medical imaging applications, have been studied extensively. Attention has been given to single isolated transducers, for which anomalous radiation patterns have been obtained, and to transducers integrated in an array structure, where additional problems occur due to coupling effects between nearest neighbors. An experimental study of these phenomena has made it possible in both cases to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…18,19 Reference 20 gives the dispersion curves for the five lowest-order modes propagating in a PZT-4 ceramics, whose physical properties are very similar to those of the P1-60 type ceramics used in our experiments. 16 The corresponding phase and group velocities for the piezoceramic plate under investigation are plotted in Fig. 7 against the frequency.…”
Section: A the Effect Of Lamb Waves In Continuous Regimementioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Reference 20 gives the dispersion curves for the five lowest-order modes propagating in a PZT-4 ceramics, whose physical properties are very similar to those of the P1-60 type ceramics used in our experiments. 16 The corresponding phase and group velocities for the piezoceramic plate under investigation are plotted in Fig. 7 against the frequency.…”
Section: A the Effect Of Lamb Waves In Continuous Regimementioning
confidence: 99%
“…We are familiar only with experiments on this point with small piezoceramic elements, when the transversal dimensions of the radiator were comparable with its thickness. 16 The measurements demonstrated severe deviations from the piston theory predictions, consisting mainly in the occurrence of parasitic sidelobes in the radiation pattern. It was shown that these lobes were due to parasitic zero-order Lamb waves propagating in the transducer and radiating into the fluid medium.…”
Section: Introductionmentioning
confidence: 97%
“…Second, it is very important to take the ''true'' displacement profile of the transducer surface into account. In fact, experimental results concerning elementary transducer do not always agree with those obtained numerically using classical integrals 3,4 because the piston mode is generally assumed. Third, two kinds of interactions occur: mechanical interaction between the elementary transducers and acoustic interaction between the solid and the fluid media.…”
Section: Introductionmentioning
confidence: 85%
“…Many studies have been performed to provide construction rules for the design of transducers. In practical terms, design engineers require both numerical and analytical models corresponding to the performance they want to optimize, such as sensitivity, bandwidth, cross-coupling levels, and elementary directivity pattern [1], [2].…”
Section: Introductionmentioning
confidence: 99%